LENGTH VARIATION OF TRINUCLEOTIDE CAG REPEAT IN THE ANDROGEN RECEPTOR GENE IN HUMAN INFERTILE MALES - PRAFULLA S. AMBULKAR; SUNIL S. PANDE (International Journal of Pharma and Bio Sciences, 2015)
Androgens are required for normal spermatogenesis, expansion of CAG repeats in the androgen receptor (AR) gene gives rise to human male infertility. We investigated length polymorphism of CAG repeats in the androgen receptor as a possible cause of impaired spermatogenesis in patients with idiopathic male infertility in our geographical central Indian population. The CAG repeat length in exon 1 of the androgen receptor gene was studied in 60 men with idiopathic azoospermia, 90 men with oligozoospermia and in 40 fertile men. The CAG repeat region was amplified by polymerase chain reactions (PCR). The number of CAG repeat was analysed by DNA sequencing. Hormone levels (FHS, LH and Testosterone) were also measured in patients with azoospermia and oligozoospermia. In the azoospermic males, two (3.3%) had short CAG repeats and five (8.3%) had long CAG repeats. In oligozoospermic men were also had two (2.2%) short CAG repeats and two (2.2%) had long CAG repeats. FHS and LH level were significantly higher in azoospermia group than in fertile control but unable to correlate with a length of CAG repeats. The prevalence of infertile men with long CAG repeats is moderately higher in azoospermic group but not in oligozoospermic group when compared with the fertile controls. Our results suggest that short and long CAG repeat within AR gene might be affected the spermatogenesis in males.